Seasonal fires shape the germinable soil seed bank community in eastern Mediterranean woodlands. (26th June 2021) - Manela, Neta; Shemesh, Hagai; Osem, Yagil; Carmel, Yohay; Soref, Chanoch; Tsafrir, Anat; Ovadia, Ofer
Abstract: We explored if and how seasonal fires interact with microhabitat type (i.e. under Pistacia shrub, under Cistus shrub or a canopy gap) to influence the composition of the germinable soil seed bank (GSSB) community in a typical eastern Mediterranean woodland. We conducted a field experiment, involving prescribed spring and autumn burns, and thereafter quantified the seed germination patterns using soil samples collected from both burned and adjacent unburned control plots. Soil temperature was significantly higher during autumn burns, while being more variable during spring burns. Fire caused overall reductions in GSSB density, richness and diversity. The reductions in GSSB richness and diversity were significantly stronger under Pistacia and Cistus shrubs located within plots subjected to autumn burns, and these patterns were mainly evident among annuals. GSSB density of dwarf shrubs was higher in samples collected from burned plots, and this pattern was more pronounced in samples collected under Pistacia and Cistus shrubs. Together with the appearance of unique species, seasonal fires led to significant changes in the composition of the GSSB community. Our results illustrate that seasonal fires interact with spatial heterogeneity to influence the composition of the GSSB community mostly via differential effects on the germination densities of annuals and dwarf shrubs. These findings imply that the increase in the frequency of seasonal fires, which has occurred in the eastern Mediterranean basin during the last few decades, may translate into a shift in eco-evolutionary selection pressures, operating on plants inhabiting this unique ecosystem.